Amish celebrations : four stories - Wiseman, Beth, 1962- (Zondervan, 2018)
The gift of sisters: Hannah and Elizabeth are fraternal twins approaching their sixteenth birthday--a time when they will be allowed to spread their wings and enjoy their rumschpringe. The sisters couldn't be more different: Hannah is outgoing and beautiful, while Elizabeth is shy and withdrawn. And when newcomer Abraham Stoltzfus arrives in Lancaster County, both women fall head over heels for him, each fighting for his affections in their own ways and driving the sisters to turn on each other. Who will Abraham choose? And will Hannah and Elizabeth reunite after a devastating heartbreak?